Hemorrhage Expansion After Pediatric Intracerebral Hemorrhage. Issue 2 (February 2021) - Boulouis, Gregoire; Hak, Jean-François; Kerleroux, Basile; Benichi, Sandro; Stricker, Sarah; Gariel, Florent; Alias, Quentin; Bourgeois, Marie; Meyer, Philippe; Kossorotoff, Manoelle; Garzelli, Lorenzo; Garcelon, Nicolas; et al.
Abstract : Background and Purpose: Significant hemorrhage expansion (sHE) is a known predictor of poor outcome after an intracerebral hemorrhage (ICH) in adults but remains poorly reported in children. In a large inception cohort, we aimed to explore the prevalence of sHE, its associations with clinical outcomes, and its clinical-imaging predictors in children. Methods: Children admitted between January 2000 and March 2020 at a quaternary care pediatric hospital were screened for inclusion. Sample was restricted to children with 2 computed tomography scans within 72 hours of ICH onset, and a minimal clinical follow-up of months. sHE was defined as an increase from baseline ICH volume by 6 cc or 33% on follow-up computed tomography. Clinical outcome was assessed at 12 months with the King's Outcome Scale for Childhood Head Injury score and defined as favorable for scores ≥5. Results: Fifty-two children met inclusion criteria, among which 8 (15%) demonstrated sHE, and 18 (34.6%) any degree of expansion. Children with sHE had more frequent coagulation disorders (25.0% versus 2.3%; P =0.022). After multivariable adjustment, only the presence of coagulation disorders at baseline remained independently associated with sHE (adjusted odds ratio, 14.4 [95% CI, 1.04–217]; P =0.048). sHE was independently associated with poor outcome (King's Outcome Scale for Childhood Head Injury <5A, odds ratio, 5.77 [95% CI, 1.01–38.95]; P =0.043). Conclusions: sHE is a frequent phenomenon after admission for a pediatric ICH and more so in children with coagulation defects. As sHE was strongly associated with poorer clinical outcomes, these data mandate a baseline coagulation work up and questions the need for protocolized repeat head computed tomography in children admitted for pediatric ICH. Abstract : Supplemental Digital Content is available in the text.